Concept of Sorrow in Uzbek Literary Context (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the intricate emotional concepts and highlighting their significance in shaping social interactions, identity, and communal values. Drawing on ethnographic studies and cultural analyses, we examine how emotions are expressed, understood, and valued in various contexts, including family dynamics, traditional celebrations, and everyday life. By understanding these emotional frameworks, we gain deeper insights into the Uzbek worldview and the ways in which emotions serve as a bridge between individual experiences and collective identity. This study contributes to the broader discourse on cultural psychology and emotional intelligence, emphasizing the importance of contextualizing emotional concepts within specific cultural narratives.